JK Lasser's New Rules for Estate, Retirement, and Tax Planning, 6th Edition - Welch, Stewart; Busby, J. (Wiley, 2019)
The popular handbook to estate planning, now updated for 2018 Since its first publication in 2002, New Rules for Estate, Retirement, and Tax Planning has sold more than 40,000 copies, providing a solid, accessible introduction to estate planning for any age or income bracket. Now in its sixth edition, Estate, Retirement, and Tax Planning continues this tradition, covering such topics as trusts, donations, life insurance, and wills in easy-to-understand language that offers valuable insights and solid strategies to help you preserve your wealth and plan your estate so that your assets go where you want with a minimum of taxes and government interference. This comprehensive guide answers such common questions as: How much do I need to retire comfortably? How do I protect my children's inheritance? How do I ensure planned donations are made after I'm gone? And many more. The Sixth Edition is also fully updated to reflect changes following the 2018 Tax Cuts and Jobs Act, so that you can learn how new regulations could impact your inheritance and trusts. Other notable features include advice on working with elderly parents and introducing financial planning to children and teenagers, in addition to a list of professional advisers and a glossary of estate planning terms. Understand estate planning and obtain solid strategies for growing your wealth Explore asset protection and succession planning strategies Discover how recent updates to the tax code could affect you and your heirs Stay informed of any relevant law changes with an author-managed web site Estate, Retirement, and Tax Planning contains a wealth of valuable information for any adult who needs help planning their financial future, from the established professional heading toward retirement, to the young adult looking to understand the basics. Wherever you are in your journey, use Estate, Retirement, and Tax Planning to ensure your legacy is protected.